2019
DOI: 10.1021/acs.orglett.9b04148
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Decarboxylative Alkylation of Titanium(IV) Enolates with Diacyl Peroxides

Abstract: Simple treatment of chiral titanium(IV) enolates with diacyl peroxides produces highly diastereoselective decarboxylative alkylations to efficiently deliver the corresponding adducts, most of which are not accessible through any of the current alkylating procedures. Such an unprecedented alkylation proceeds through a SET process that triggers the decomposition of the peroxide into a carbon-centered radical that finally combines with the resulting Ca radical. The procedure has been applied to the enantioselecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Taking advantage of our experience, we were pleased to observe that the titanium(IV) enolate of ( S ) 4-benzyl-5,5-dimethyl- N -propanoyl-1,3-oxazolidin-2-one ( 1 in Table 1 ) reacted with the tert -butyl perester from 1-adamantanecarboxylic acid ( a in Table 1 ) under mild conditions similar to those employed for the alkylation with diacyl peroxides. 12 Indeed, the alkylated adduct 1a was isolated with a high yield and an excellent diastereoselectivity (74% and dr 97:3, see Table 1 ) through the simple stirring of a mixture of the titanium(IV) enolate of 1 with 1.5 equiv of a in 1,2-dichloroethane for 1.5 h at room temperature. Slight variations of such conditions also gave the desired adduct 1a but in lower yields ( Table 1 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Taking advantage of our experience, we were pleased to observe that the titanium(IV) enolate of ( S ) 4-benzyl-5,5-dimethyl- N -propanoyl-1,3-oxazolidin-2-one ( 1 in Table 1 ) reacted with the tert -butyl perester from 1-adamantanecarboxylic acid ( a in Table 1 ) under mild conditions similar to those employed for the alkylation with diacyl peroxides. 12 Indeed, the alkylated adduct 1a was isolated with a high yield and an excellent diastereoselectivity (74% and dr 97:3, see Table 1 ) through the simple stirring of a mixture of the titanium(IV) enolate of 1 with 1.5 equiv of a in 1,2-dichloroethane for 1.5 h at room temperature. Slight variations of such conditions also gave the desired adduct 1a but in lower yields ( Table 1 ).…”
mentioning
confidence: 99%
“…At this point, we carried out a comprehensive theoretical study to unveil the origin of the observed reactivity and selectivity. As for the reaction with diacyl peroxides, 12 DFT calculations 20 of the alkylation of 1 with perester a indicated that it also may proceed through an electron transfer from I ( Scheme 4 ), the biradical form of titanium enolates, 11 to the σ* of the O–O bond of a . Thus, a single-electron transfer (SET) redox reaction causes the formation of the Ti(IV) radical II by a one electron loss and triggers the cleavage of the O–O bond, which produces an oxygen radical and an oxygen anion species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination of Ti­(O i Pr) 4 with 1a produces a certain amount of free isopropoxy anion, and the Michael addition of the anion to activated 1a results in enolate intermediate I , which has a resonance structure of II . Then the valence tautomery between Ti­(IV) and the enolate leads to Ti­(III) and III . The regioselective attack of III to 1a produces IV , and the corresponding cleavage generates alkynyl formal radical V and olefin VI .…”
mentioning
confidence: 99%